A scoping Review of tools used to assess patient Complexity in rheumatic disease. (17th February 2021) - Hawker, Kara; Barnabe, Cheryl; Barber, Claire E.H.
Abstract: Objective: Patients with rheumatic diseases often have multiple comorbidities which may impact well‐being leading to high psychosocial complexity. This scoping review was undertaken to identify complexity measures/tools used in rheumatology that could help in planning and coordinating care. Methods: MEDLINE, EMBASE and CINAHL were searched from database inception to 14 December 2019 using keywords and Medical Subject Headings for "care coordination", "complexity" and selected rheumatic diseases and known complexity measures/tools. Articles describing the development or use of complexity measures/tools in patients with adult rheumatologic diagnoses were included regardless of study design. Included articles were evaluated for risk of bias where applicable. Results: The search yielded 407 articles, 37 underwent full‐text review and 2 were identified during a hand search with 9 included articles. Only 2 complexity tools used in populations of adult patients with rheumatic disease were identified: the SLENQ and the INTERMED. The SLENQ is a 97‐item patient needs questionnaire developed for patients with systemic lupus (n = 1 study describing tool development) and applied in 5 cross‐sectional studies. Three studies (a practice article, trial and a cross‐sectional study) applied the INTERMED, a clinical interview to ascertain complexity and support coordinated care, in patients with rheumatologic diagnoses. Conclusions: There is limited information on the use of patient complexity measures/tools in rheumatology. Such tools could be applied to coordinate multidisciplinary care and improve patient experience and outcomes. Patient contribution: This scoping review will be presented to patient research partners involved in co‐designing a future study on patient complexity in rheumatic disease.